The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1108/ijccsm-03-2017-0060
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of adaptation, resilience and climate knowledge in the Pacific

Abstract: Purpose While the South Pacific is often cited as highly vulnerable to the impacts of climate change, there is comparatively little known about how different groups perceive climate change. Understanding the gaps and differences between risk and perceived risk is a prerequisite to designing effective and sustainable adaptation strategies. Design/methodology/approach This research examined three key groups in Samoa, Fiji and Vanuatu: secondary school teachers, media personnel, and rural subsistence livelihood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 49 publications
0
24
0
Order By: Relevance
“…The papers included show that different island groups have different priorities and needs, which are often not accounted for. Instead climate change programs tend to didactically pass down directives and crowd out issues which are perceived as greater local concerns (Baldacchino & Kelman, 2014;Walshe et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…The papers included show that different island groups have different priorities and needs, which are often not accounted for. Instead climate change programs tend to didactically pass down directives and crowd out issues which are perceived as greater local concerns (Baldacchino & Kelman, 2014;Walshe et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Finally, it was found that there is a number of variables which measure peripherality by the types of knowledges routinely used/accessed for decision-making by communities that in turn help identify their resilience-dependence character, something critical to measuring peripherality in many contexts (Felzensztein et al 2013;Nunn and Kumar 2018). The number of mobile phones per capita, while admittedly not adequately capturing global knowledge access/use in Bua, is nevertheless considered key to measuring peripherality; a stage is likely to be reached in the future when novelty/social uses of mobile phones may be replaced by largely practical ones (Walshe et al 2018; Watson and Duffield 2016). The use of (and implicit trust in) traditional versus 'western' healthcare is also considered a measure of actual peripherality (rather than simply distance along a core-periphery gradient).…”
Section: Identifying Proxy Measures Of Peripherality For Bua Communitiesmentioning
confidence: 99%
“…Risk management is, therefore, the modulated mental models and the psychological mechanisms that people use to judge, evaluate, tolerate, and react to risks [16]. Furthermore, it is how individuals and communities perceive the complex and varied factors which interfere in risk perception, such as social networks and capital, media influence, personal experience, values, worldviews, and the influence of individual adaptation strategy through learning from past events [17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%